Records of sunspots and aurora candidates in the Chinese official histories of the Yuán and Míng dynasties during 1261–1644. (22nd July 2017) - Hayakawa, Hisashi; Tamazawa, Harufumi; Ebihara, Yusuke; Miyahara, Hiroko; Kawamura, Akito Davis; Aoyama, Tadanobu; Isobe, Hiroaki
Abstract: Records of observations of sunspots and auroras in pre-telescopic historical documents provide useful information about past solar activity both in long-term trends and short-term space weather events. In this study, we present the results of a comprehensive survey of the records of sunspots and aurora candidates in the Yuánshĭ and Míngshĭ, Chinese Official Histories spanning 1261–1368 and 1368–1644, based on continuous observations with well-formatted reportds conducted by contemporary professional astronomers. We then provide a brief comparison of these data with Total Solar Irradiance (TSI) as an indicator of the solar activity during the corresponding periods to show significant active phases between the 1350s–80s and 1610s–30s. We then compared the former with contemporary Russian reports concerning naked-eye sunspots and the latter with contemporary sunspot drawings based on Western telescopic observations. Especially some of the latter are consistent with nitrate signals preserved in ice cores. These results show us some insights on and beyond minima and maxima of solar activity during the 13 th –17 th centuries.